Stretchable and self-healable lithium-ion batteries with all-in-one configuration - Zhen Li; Yue Guo; Xiaokong Liu (Supramolecular Materials)
Stretchable lithium-ion batteries (LIBs) are highly desirable to serve as the power sources of stretchable and wearable electronic devices. Furthermore, endowing stretchable LIBs with self-healability can prolong their life-time and enhance their reliability. However, previously reported self-healable LIBs were flexible rather than stretchable, while the stretchable LIBs were unable to self-heal. Herein, we present a novel strategy to fabricate stretchable and self-healable LIBs with all-in-one configuration, by exploiting dynamic covalent polymers as both the electrolyte and the binder of electrodes. The developed polymer electrolyte exhibits a room-temperature ionic conductivity as high as 3.6 × 10−4 S cm−1 and possesses an elongation-at-break of 250 ± 30 %. Moreover, the stretchable electrolyte is highly resilient and its ionic conductivity shows minimal changes at different strains. The electrolyte exhibits an autonomous self-healing property at room temperature, making the cut sample easily recover its original performance. Importantly, the electrolyte and electrodes can be fused together at the interface to construct a healable LIB with all-in-one configuration, through the exchange of the dynamic imine bonds that exist in both the electrolyte and electrodes. As a result, the as-developed LIB possesses an elongation-at-break of 220 ± 20 % and can supply power in the course of stretching and releasing. Furthermore, the cut and then healed LIB can still deliver an average discharge capacity of 126.4 mAh g − 1 and steadily provide power for LED. This work offers a new avenue for the development of stretchable and self-healable LIBs for the stretchable and wearable electronic devices.